Income Diversification and Poverty Among Rural Farm Households in Southwest Nigeria (2011)
Rural development has been erroneously equated to agricultural development. The former works to diversify income through non-farm activities to complement proceeds of the latter. However, the actual role of non-farm income in poverty alleviation is not yet known among rural households. There is therefore the need to critically explore the roles of non-farm income diversification in rural poverty alleviation. The patterns and contributions of non-farm income diversification to poverty reduction among rural farm households in Southwest Nigeria were investigated. A multistage sampling technique was used to obtain data from rural farm households. Three states (Ekiti, Ogun and Osun) from the six south western states were randomly selected. Five agricultural zones were randomly selected from the three states based on probability proportionate to size. In each zone, four blocks and three cells per block were selected. Lastly, two farming communities per cell and four farming households per community were selected to make 480 farming households. Structured questionnaire was used to collect data on socio-economic characteristics, household assets, income generating activities, labour-use, income and expenditure. Descriptive statistics, Foster-Greer-Thorbecke poverty measures, Herfindal index, Tobit and Probit regression methods were employed for data analyses at p = 0.05. Mean age of household heads, household size and dependency ratio were 49.9 ± 0.6 years, 6.8 ± 0.1 and 0.7 ± 0.1, respectively. The mean year of schooling of household heads was 8.8 ± 0.2 and 83.7% of households were headed by male. The mean per capita income was N206.7 ± 160.3/day while the per capita cost of basic needs was N253.4 ± 28.6/day. The incidence, depth and severity of poverty were 76.4%, 32.9% and 17.3% respectively. Ninety four percent of the households derived their income from a diversified portfolio of livelihood activities, with non-farm activities accounting for 67.1% of the income. The non-farm activities included skilled (18.0%) and unskilled (22.9%) wage employment, self-employment (81.3%) and social and community service (8.8%). Self-employment was the largest non-farm income source contributing 42.1%. Involvement in non-farm labour activities was significantly higher among poor than non-poor farm households. The level of income diversification depicted by Herfindal index was 2.8 ± 0.04 and it was significantly higher among poor than non-poor farm households. The implicit wage rate of household labour use in farming activities (N1,773.4/manday) was significantly higher than in non-farm activities (N878.0/manday). Education (0.1) and electricity (0.5) significantly increased non-farm income diversification while distance to urban centre (-0.04), landholding (-0.6) and animal asset base (-0.2) significantly reduced non-farm income diversification. Participation in non-farm skilled (-0.1) and unskilled (-0.1) wage employments significantly reduced the probability of being poor. Other characters of respondents that significantly reduced the probability of being poor included education (-0.1), landholding (-0.4), investment asset base (-0.000005) and rural electricity (-0.1) while household size (0.1) increased the probability. Participation in skilled and unskilled wage employment significantly reduced poverty among rural farm households in Southwest Nigeria.